Ethics, Morals and Morals and Factors Affecting Ethics - Shanshan Xu; Murphy Xavier; McCarty Elliot (Sharia Oikonomia Law Journal, 2023)
Human life can never be separated from binding values, rules and norms. In this life, humans show their ethics, morals and also their manners in socializing. Ethics are very important for all areas of human life, including in business. Islam as a religion that is very concerned about its people has also provided clear rules regarding ethics, morals and manners. The purpose of this paper is to discuss Ethics in Islam. Ethics in language is the science of what is bad and about moral rights and obligations. Ethics also means the values of right and wrong that a person holds. Ethics means manners or social behavior. The basic meaning of ethics is ethos (Greek).Ethics is part of the science of philosophy. Ethics is often equated with ethics and morals, but many experts also distinguish between the two.The method of this writing is the Lebrary Riseach method. In this paper the author discusses the definition of ethics, the urgency of ethics, factors that influence ethics, the Koran and hadith in ethics.